Erratum: Simplified Analytical Pushover Method for Precast Segmental Concrete Bridge Columns (Vol. 16, 805–822, 2013). Issue 6 (June 2013) - Bu, Zhan-Yu; Ou, Yu-Chen
In page 807 paragraph 1 line 7, there was an error with the figure name, the correct version appears below: column enters the second stage [Figure 1(b)]. In page 812, there was an error with equation 25. The correct version appears below: (25) Δ 1 = 1 3 ϕ 1 H 2